Basic strength properties of a few selected Malaysian bamboos - Abang Ali, Abang Abdullah; Abang Ali, Abang Abdul Rahim (Institusi Jurutera Malaysia, 1984)
There is now a growing interest in low-cost materials of construction, to reduce dependence on the traditional engineering materials. An experimental investigation at Universiti Pertanian Malaysia have shown that bamboo has a potential in becoming an important engineering material in the near future, especially with the current rate of utilization of timber. The results of a series of tests to obtain the basic strength properties of a few selected Malaysian bamboos is presented.